Cytotoxic Effects of Al-Yohedia Municipal Waste Water - Wassan M. A. Al-Morshidy1 , Hussein O.M. Al-Dahmoshi2 , Ayad M. J. Al-Mammori3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Household waste water represent an hazardous reservoir for wide range of medically important pathogensthan can push an alarm on public health threatening diseases. It contain toxic materials, hazardous heavymetals and different pathogens. The study includes investigation of microbial, environmental, pathologicaland molecular effects of waste water. The results of dissolved heavy metals concentration revealed high Niconcentration (Mean±SD of four sites were 119.675±0.778 mg/L), high Mn concentration (Mean±SD of foursites were 108.2±1.095 mg/L), high Fe concentration (Mean±SD of four sites were 119.675±0.740.475±1.228mg/L), high Cd concentration (Mean±SD of four sites were 13.75±1mg/L), high Cu concentration (Mean±SDof four sites were 5±0.755mg/L) with no significant differences in concentration among four sites for Ni andCu while difference noted among Mn, Fe and Cd. Results of microbial study revealed that the Mean±SD ofCFU/ml were 1.97x1010±0.543 and the microbes were E. coli, K. pneumoniae, P. aeruginosa, V. cholerae,V. parahaemolyticus, S. aureus, E. faecalis, C. albicans, C. krusei and C. glabrata with MAR index rangedfrom (0-1). DNA damage results using comet assay for revealed that high level of damage to DNA of ratdosed with waste water compared with those dosed with fresh water in both tail length (11.35±2.1, 2.7±0.9)and tail moment (1.193±0.11, 0.2±0.1) respectively. Immunohistochemistry (IHC) assay was used to detectof 8-OHDG among liver tissues of rat dosed with waste water (study) and fresh water (control) and theresults revealed strong signal (high expression) in all liver tissues of rat dosed with waste water (study)compared with those dosed with fresh water (control) whose gave negative results. Histopathological resultsof eat dosed with waste water compared with those dosed with fresh water (control) were observed after 60days of dosing. the results displayed that the control was normal where mild chronic hepatitis showed insamples of site 1, 2, 3 while site4 had moderate chronic hepatitis and Fasciola hepatica. The current studyconclude that, Al-Yohedia Municipal wastewater is very dangerous and have different clinically importantpathogens along with different cytotoxic materials.